2015
DOI: 10.1159/000441364
|View full text |Cite
|
Sign up to set email alerts
|

Paricalcitol, Microvascular and Endothelial Function in Non-Diabetic Chronic Kidney Disease: A Randomized Trial

Abstract: Background: Vitamin D deficiency, sympathetic activation and endothelial dysfunction are associated with increased cardiovascular risk in patients with chronic kidney disease (CKD). Studies have so far failed to establish the role of vitamin D and vitamin D receptor activator (VDRA) treatment in moderate CKD. This trial was designed to assess whether VDRA treatment can ameliorate sympathetic activation and macro- and microvascular dysfunction in non-diabetic patients with moderate CKD. Methods: We conducted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 39 publications
6
56
2
2
Order By: Relevance
“…In line with our results, Wu‐Wong et al have reported that paricalcitol can improve endothelial‐dependent relaxation in uremic rats independent from effects on PTH serum concentration 16, 17. Recently, randomized clinical trials conducted in patients with CKD also demonstrated that treatment with active vitamin D leads to significantly favorable changes in endothelial function 18, 19, 33, 34, 35…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with our results, Wu‐Wong et al have reported that paricalcitol can improve endothelial‐dependent relaxation in uremic rats independent from effects on PTH serum concentration 16, 17. Recently, randomized clinical trials conducted in patients with CKD also demonstrated that treatment with active vitamin D leads to significantly favorable changes in endothelial function 18, 19, 33, 34, 35…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, while in vitro studies suggested a protective role for vitamin D in ameliorating damaged endothelium,12, 13 experimental in vivo CKD studies have primarily focused on the prevention of vascular calcification of the medial layer and heart failure9, 14, 15 but paid little attention to structural endothelial damage. A small number of prior studies have suggested benefits of the active vitamin D analogue paricalcitol on endothelial stability in animal models of CKD16, 17 and even in patients 18, 19. Interestingly, paricalcitol supplementation increased kidney and serum α‐Klotho levels in in vivo models of CKD 20, 21.…”
Section: Introductionmentioning
confidence: 99%
“…In the randomized SOLID trial [17], we recently demonstrated that treatment with a vitamin D receptor activator (VDRA)- paricalcitol, in patients with moderate CKD was associated with preserved micro- and macro-vascular endothelial function and microcirculation. In this study, we therefore hypothesized that this effect is a consequence of changes in pro-inflammatory cytokines, and altered up-stream gene expression regulators, assessed by plasma miRs.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the PRIMO study [16], Wang et al [13] found no difference in LV mass in with paricalcitol in stage 3–5 CKD patients. Suggesting that endothelial dysfunction is at least partially reversible in CKD patients and vitamin D supplementation may yet exert favorable effects on the cardiovascular system, two trials identified improvement in endothelial function with paricalcitol use [14, 15]. Consistent with prior studies suggesting that vitamin D can reduce proteinuria both through RASS-dependent and RAAS-independent pathways [17], Molina et al [18] identified a significant decrease in proteinuria in CKD patients treated with cholecalciferol for 6 months.…”
Section: Introductionmentioning
confidence: 86%